(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the application of the principles of the concept of TQM (Total Quality Management) in improving the quality management system of education in pedagogical higher educational institutions and the development of its scientific and methodological support. The essence of the concepts is revealed on the basis of modern research; the principles of research specific to the system of education quality management are pedagogically interpreted on the basis of the author’s approach; pedagogy educational institutions developed quality management system functional structure, management, and ensuring the effectiveness of teaching conditions specified in the quality of education.